Image Light Distribution in the Multiview 3-D Imaging System - Son, Jung-Young; Vashpanov, Yuriy; Kim, Moon-Seok; Park, Min-Chul; Kim, Jai-Soon (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2010)
The light intensity distributions in the front space of a contact-type multiview 3-D imaging system are measured to estimate the effects of the differences in real and nominal values of parameters and alignment errors on the quality of 3-D images. The distributions clearly reveal how the viewing zone cross section is formed and how the mixed images are formed. For these measurements, a 1 x 4 Fresnel lens array and a projector are used as the viewing zone forming optics and image source, respectively. The results are graphically represented in terms of crosstalk. Both the misalignments and the inaccuracies greatly increase the crosstalk.
Keywords: BARRIER